Caffeine inhibits STAT1 signaling and downregulates inflammatory pathways involved in autoimmunity - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
Caffeine is a widely consumed pharmacologically active product. We focused on characterizing immunomodulatory effects of caffeine on peripheral blood mononuclear cells. Caffeine at high doses showed a robust downregulatory effect on cytokine activity and genes related to several autoimmune diseases including lupus and rheumatoid arthritis. Dose-dependent validation experiments showed downregulation at the mRNA levels of key inflammation-related genes including STAT1, TNF, IFNG, and PPARG. TNF and PPARG were suppressed even with the lowest caffeine dose tested, which corresponds to the serum concentration of caffeine after administration of one cup of coffee. Cytokine levels of IL-8, MIP-1 beta, IL-6, IFN-gamma, GM-CSF, TNF, IL-2, IL-4, MCP-1, and IL-10 were decreased significantly with caffeine treatment. Upstream regulator analysis suggests that caffeine inhibits STAT1 signaling, which was confirmed by showing reduced phosphorylated STAT1 after caffeine treatment. Further studies exploring disease-modulating potential of caffeine in autoimmune diseases and further exploring the mechanisms involved are warranted.
Keywords: Caffeine; Autoimmunity; Inflammation; Cytokine; TNF; Rheumatoid; Lupus; SYSTEMIC-LUPUS-ERYTHEMATOSUS; TUMOR-NECROSIS-FACTOR; NAIVE CD4+T CELLS; RHEUMATOID-ARTHRITIS; DISEASE-ACTIVITY; LETHAL AUTOIMMUNITY; GAMMA EXPRESSION; B-LYMPHOCYTE; T-CELLS; CHEMOKINE